Outbreak Of COVID-19 In Nepal: An Overview of The First 1042 Cases and Public Health Response - Pandey, Udesh (Journal of Karnali Academy of Health Sciences, 2020)
Background: COVID-19 caused by SARS-CoV-2 originated from Wuhan, China has caused a worldwide pandemic of which Nepal is not an exception. Nepal got its first case on January 2, 2020, and as of May 28, 2020, a total number of 1042 cases, from 51 districts are reported to be positive on RT-PCR. After an initial gap of about 2 months between first and second confirmed cases, cases have shown a rapid increase in number despite continued nationwide lockdown. This report presents major events in the timeline of the outbreak, an overview of first 1024 cases and analysis of their epidemiological features.Methods: Relevant data concerning COVID-19 cases and RT-PCR tests were derived from daily situation reports as published by the Ministry of Health and Population. It was compared with global data and population structure of the country.Results: When compared with initial reports from China, the proportion of asymptomatic cases are much higher and compared with global data mortality rate is very low (6.5% worldwide vs 0.45% in Nepal).Younger age group in their 20s and 30s are disproportionately affected than older age groups. Males (77%) are affected much more than females (23%).Conclusion: The rate of laboratory testing with RT-PCR has increased significantly but serological antibody tests should be used with caution. In upcoming days, a massive mobilization of resources may be required across the country to contain the infection and treat moderately and critically ill patients